2018
DOI: 10.1002/chem.201804099
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantio‐ and Diastereoselective Mannich Addition of TosMIC to Ketimines

Abstract: Chiral amines bearing a stereocenter in the α position are ubiquitous compounds with many applications in the pharmaceutical and agrochemical sectors, as well as in catalysis. Catalytic asymmetric Mannich additions represent a valuable method to access such compounds in enantioenriched form. This work reports the first enantio‐ and diastereoselective addition of commercially available p‐toluenesulfonylmethyl isocyanide (TosMIC) to ketimines, affording 2‐imidazolines bearing two contiguous stereocenters, one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(25 reference statements)
1
16
0
Order By: Relevance
“… 40 Variation in the pronucleophile component was also studied, and p -toluenesulfonyl isocyanide (TosMIC) was a competent pronucleophile for the Mannich transformation with a variety of DPP-protected imines ( Figure 4 g). 41 …”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 Variation in the pronucleophile component was also studied, and p -toluenesulfonyl isocyanide (TosMIC) was a competent pronucleophile for the Mannich transformation with a variety of DPP-protected imines ( Figure 4 g). 41 …”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 99%
“…In the more recent report using TosMIC as the pronucleophile, DFT was used to rationalize the formation of the major enantiomer ( Figure 4 h). 41 In the two lowest-energy transition states, in which the ketimine adopts the E -configuration, the strongly hydrogen bond-accepting phosphine oxide interacts with both silver and the amide of the ligand through hydrogen bonding.…”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 99%
“…However, Trulli and colleagues have shown that presence of a steric hindrance on the pronucleophile carbon of α-substituted methyl isocyanoacetates leads to formation of both isomers (Scheme 48 Franchino et al applied catalytic Mannich addition of TosMIC 1m to N-phosphonyl ketimines 99 in the presence of silver(I) oxide and N,P-ligands 16 for enantio-and diastereoselective preparation of 5-alkyl-5-aryl-4-tosyl-2-imidazolines 100 in high yields and stereopurity. [60] Computational analysis confirmed the key role of silver oxide-N,P-ligands complexes in streoselectivity of the reaction and substrate activation during C-C bond formation (Scheme 49). N-phosphonyl imines 101 were also involved in sterecontrolled preparation of N-phosphonyl-4-carboxymethyl-5-aryl-(alkyl)-2-imidazolines 102, 103 described by Qiao and colleagues.…”
Section: Transition-metal Catalyzed [3+2] Cycloadditionmentioning
confidence: 81%
“…Franchino et al applied catalytic Mannich addition of TosMIC 1m to N‐phosphonyl ketimines 99 in the presence of silver(I) oxide and N,P‐ligands 16 for enantio‐ and diastereoselective preparation of 5‐alkyl‐5‐aryl‐4‐tosyl‐2‐imidazolines 100 in high yields and stereopurity. [ 60 ] Computational analysis confirmed the key role of silver oxide‐N,P‐ligands complexes in streoselectivity of the reaction and substrate activation during C–C bond formation (Scheme 49).…”
Section: [3+2]‐cycloaddition Of Activated Methylene Isocyanidesmentioning
confidence: 86%
“…All compounds were characterized by spectroscopic analysis and stereoselectivity was confirmed by computation approach and X-ray diffraction method. [17] A. M. van Leusen and his co-workers reported the synthesis of imidazole derivatives from aldimine derivative and tosylmethyl isocyanide. Diverse range of aldimines was prepared from readily available aldehyde and N-dimethylsulfamoyl amide in refluxing toluene.…”
Section: Synthesis Of Imidazole Scaffoldmentioning
confidence: 99%